Paraurethral cyst. A case report - Emilio Vega Azcúe (Medisur)
The paraurethral or Skene’s duct cyst, is a rare diagnostic entity in a newborn. It represents less than 0,5 % of congenital malformations of the urinary tract. All over the world it is reported an incidence of 1:2000 to 1:7000 in female births. In the newborn, the paraurethral cyst is caused by retention of secretions in the Skene's gland due to the obstruction of its ducts. Most of these cysts decrease in size during the first four to eight weeks, but they may cause symptoms of infection or urinary obstruction. They can also get formed from persistent embryonic remains of the mesonephric ducts (Wolffian duct), known as Gartner cysts and from the occlusion of unfused paramesonephric ducts (Müllerian). The case of a 25-day-old female, diagnosed with paraurethral cyst that underwent surgery and evolved successfully is presented.